2006
DOI: 10.1161/circulationaha.105.000927
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Transforming Growth Factor-β Is Associated With Increased Hyaluronan Content and Impairment of Repair in Marfan Syndrome Aortic Aneurysm

Abstract: Background— Marfan syndrome (MFS), a condition caused by fibrillin-1 gene mutation is associated with aortic aneurysm that shows elastic lamellae disruption, accumulation of glycosaminoglycans, and vascular smooth muscle cell (VSMC) apoptosis with minimal inflammatory response. We examined aneurysm tissue and cultured cells for expression of transforming growth factor-beta1 to -beta3 (TGFβ1 to 3), hyaluronan content, apoptosis, markers of cell migration, and infiltration of vascular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 19 publications
1
59
0
2
Order By: Relevance
“…Studies using transgenic mouse models of Marfan syndrome showed a critical pathogenic role for increased TGF-β signaling in promoting abnormal vessel remodeling, dilatation, and aneurysm expansion (6). The results were confirmed by studies showing upregulation of TGF-β signaling in patients with Marfan disease and by the identification of TGFBR1 and TGBR2 gene mutations in patients with Loeys-Dietz syndrome, thought to be responsible for increased TGF-β activity (7)(8)(9)(10). These studies have led at least some investigators to suggest that monogenic disorders such as Marfan and Loeys-Dietz syndromes are good genetic models for the pathogenesis of other forms of aortic aneurysm (11).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies using transgenic mouse models of Marfan syndrome showed a critical pathogenic role for increased TGF-β signaling in promoting abnormal vessel remodeling, dilatation, and aneurysm expansion (6). The results were confirmed by studies showing upregulation of TGF-β signaling in patients with Marfan disease and by the identification of TGFBR1 and TGBR2 gene mutations in patients with Loeys-Dietz syndrome, thought to be responsible for increased TGF-β activity (7)(8)(9)(10). These studies have led at least some investigators to suggest that monogenic disorders such as Marfan and Loeys-Dietz syndromes are good genetic models for the pathogenesis of other forms of aortic aneurysm (11).…”
Section: Introductionmentioning
confidence: 85%
“…The results seemed at odds with data showing increased TGF-β signaling as a driving force in the pathogenesis of Marfan syndrome (7,9,10), confirmed later by mechanistic studies showing that inhibition of TGF-β signaling prevents vessel dilatation and aneurysm formation in a mouse model of Marfan disease (6). We therefore used 2 different anti-TGF-β antibodies, including the same anti-TGF-β antibody (AB-100-NA, R&D Systems) shown to inhibit aortic aneurysm formation in a mouse model of Marfan disease (6).…”
Section: Systemic Neutralization Of Tgf-β Activity Breaks the Resistamentioning
confidence: 99%
“…Fibrillin-1 is the major structural component of the extracellular microfibrils of the ECM 10 and also seems to be involved in sequestering the growth factor TGFb in inactive form. 5,11,12 In adults, mesenchymal cells derive from stem cells residing in the bone marrow and mesenchymal tissues. 13,14 These stem cells retain the ability to differentiate into cells of connective tissue lineages, including adipocytes, osteoblasts, chondrocytes, smooth and skeletal muscle, endothelial cells of blood vessels and fibroblasts (reviewed in Barry and Murphy 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Le [3,4]. Ces données proviennent essentiellement d'études menées chez les patients atteints du syndrome de Marfan dont la physio-1 Syndrome de Marfan : maladie génétique à transmission autosomique dominante due à une altération du tissu conjonctif.…”
unclassified
“…De façon schématique, les anévrismes syndromiques, qui correspondent aux formes familiales rencontrées dans le syndrome de Marfan 1 ou le syndrome de Loeys-Dietz 2 [2] se distinguent des formes non syndromiques, beaucoup plus fréquentes et qui compliquent les lésions athéromateuses. Plusieurs travaux menés chez l'animal et chez l'homme suggèrent que le TGF (transforming growth factor b) participe au développement de l'anévrisme [3,4]. Ces données proviennent essentiellement d'études menées chez les patients atteints du syndrome de Marfan dont la physio-1 Syndrome de Marfan : maladie génétique à transmission autosomique dominante due à une altération du tissu conjonctif.…”
unclassified